Origin of the genetic code: a testable hypothesis based on tRNA structure, sequence, and kinetic proofreading. - Hopfield, J J (1978)
We hypothesize that the origin of the genetic code is associated with the structure of the tRNA that existed in primal cells. The sequences of modern tRNA contain correlations which can be understood as "fossil" evidence of the secondary structure of primal tRNA. Kinetic proofreading through diffusion can amplify a low level of intrinsic selectivity of tRNA for its amino acid. Experimental tests of the theory are suggested.